A checklist designed to aid consistency and reproducibility of GRADE assessments: development and pilot validation - Meader, Nick (BioMed Central, 2014)
BACKGROUND: The grading of recommendation, assessment, development and evaluation (GRADE) approach is widely implemented in health technology assessment and guideline development organisations throughout the world. GRADE provides a transparent approach to reaching judgements about the quality of evidence on the effects of a health care intervention, but is complex and therefore challenging to apply in a consistent manner. METHODS: We developed a checklist to guide the researcher to extract the data required to make a GRADE assessment. We applied the checklist to 29 meta-analyses of randomised controlled trials on the effectiveness of health care interventions. Two reviewers used the checklist for each paper and used these data to rate the quality of evidence for a particular outcome. RESULTS: For most (70%) checklist items, there was good agreement between reviewers. The main problems were for items relating to indirectness where considerable judgement is required. CONCLUSIONS: There was consistent agreement between reviewers on most items in the checklist. The use of this checklist may be an aid to improving the consistency and reproducibility of GRADE assessments, particularly for inexperienced users or in rapid reviews without the resources to conduct assessments by two researchers independently.